COVID-19 Vaccination Willingness and Associated Factors in Japanese Primary Care Patients: A Cross-Sectional Study - Natsuki Kajikawa; Shoji Yokoya; Tetsuhiro Maeno (SAGE Publishing, 2022)
Introduction/Objectives: COVID-19 vaccination is important to stop the pandemic. It has been reported that willingness to be vaccinated is associated with system factors as well as individual attitudes and beliefs. Primary care patients include individuals at increased risk of poor outcomes after COVID-19 infection, such as elderly people and those with comorbidities. This study investigated attitudes in this population toward COVID-19 and COVID-19 vaccination, including willingness to be vaccinated and associated factors. This study was conducted in Japan, where the population has low vaccine confidence, during the initial phase of COVID-19 vaccination. Methods: Patients from 1 primary care clinic in Kitaibaraki City, Ibaraki, Japan, participated in this study from March to April 2021. They were administered a self-reported questionnaire exploring factors such as willingness to undergo COVID-19 vaccination, perceived susceptibility, and perceived vaccine efficacy. Multivariable logistic regression analysis was conducted to identify factors associated with vaccination. Results: Of the 717 patients (response rate, 88.3%), 512 (70.0%) reported they were willing to be vaccinated for COVID-19. Multivariate analysis revealed that vaccination willingness was associated with older age (odds ratio [OR] 1.03, 95% confidence interval [CI] 1.01-1.05), male gender (OR 1.95, 95% CI 1.15-3.30), influenza vaccination in in the 2020/2021 season (OR 2.54, 95% CI 1.49-4.32), recommendation from others (OR 3.11, 95% CI 1.58-6.18), high perceived susceptibility (OR 2.51, 95% CI 1.45-4.33), belief in vaccine efficacy (OR 3.83, 95% CI 1.54-9.56), high perceived susceptibility to vaccine-related adverse events (OR 0.37, 95% CI 0.22-0.64), and high espousal of social norms (OR 8.00, 95% CI 2.78-23.0). Conclusions: COVID-19 vaccination was widely acceptable to Japanese primary care patients. In addition to factors such as vaccine efficacy, and past influenza vaccination, social norms may be important in determining COVID-19 vaccination willingness.